2014
DOI: 10.1088/1054-660x/24/4/045603
|View full text |Cite
|
Sign up to set email alerts
|

Cationic porphyrin derivatives for application in photodynamic therapy of cancer

Abstract: Current studies in photodynamic therapy (PDT) against cancer are focused on the development of new photosensitizers (PSs), with higher phototoxic action. The aim of this study was to compare the therapeutic efficiency of tri-cationic meso-substituted porphyrin derivatives (Tri-Py + -Me-PF, Tri-Py + -Me-Ph, Tri-Py + -Me-CO 2 Me and Tri-Py + -Me-CO 2 H) with the well-known tetra-cationic T 4 PM. The phototoxic action of these derivatives was assessed in human colon adenocarcinoma cells by cell viability, intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Several porphyrins are now approved for a variety of diseases, including cancers [149,150,151] and age-related macular degeneration [152,153].…”
Section: Other Applications Of Porphyrinsmentioning
confidence: 99%
“…Several porphyrins are now approved for a variety of diseases, including cancers [149,150,151] and age-related macular degeneration [152,153].…”
Section: Other Applications Of Porphyrinsmentioning
confidence: 99%
“…–Ph, –PF and –CO 2 Me compounds were more photochemically active than T 4 PM and –CO 2 H compounds after light activation, causing cell apoptosis in the human colon adenocarcinoma cell line Caco-2. This study showed that the nature of the peripheral substituent at the meso -position is very important for potent photocytotoxicity, and –Ph, –PF and –CO 2 Me porphyrin derivatives were good PSs for PDT [ 60 ].…”
Section: Porphyrin and Chlorin Derivatives For Pdt Treatment Of Colorectal Cancermentioning
confidence: 99%
“…PS toxicity is not appreciated unless oxidative stress occurs in response to its activation [125,141]. In addition to eliciting direct cytotoxic effects [142][143][144][145][146][147] and vascular damage [148], PDT also induces immunological reactions [20,[149][150][151]. PDT outcome has been associated with the subcellular localization of PSs [146,[152][153][154] and the PDT dose delivered, leading to tumor cell photodamage through four, not mutually exclusive, cell death pathways, such as apoptosis, necrosis, autophagy, and paraptosis, which could differentially stimulate the host immune system [155].…”
Section: Photodynamic Therapymentioning
confidence: 99%